2019
DOI: 10.1177/0018726719894633
|View full text |Cite
|
Sign up to set email alerts
|

The affective commons of Coworking

Abstract: What kind of common project is Coworking? Coworking was first presented as a novel model for organising autonomous, authentic and creative labour amid a community of workers who share these progressive aspirations. That this promise has not always been realised in practice has provoked a strong sense of ambivalence among many Coworkers. This article offers a critical assessment of this ambivalence, which we approach by way of a novel theoretical category, an affective commons. Such a commons describes the atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 85 publications
0
62
0
1
Order By: Relevance
“…Recent literature on coworking highlighted the role of socially motivated community-building in these novel workspaces. Coworkers generate more than a ‘sense of community’ (Garrett et al, 2017), namely also rituals, routines and mechanisms of co-discipline that produce a degree of organizationality (Blagoev et al, 2019) and an ‘affective commons’ (Waters-Lynch & Duff, 2019) understood as affective atmospheres acting as ‘manifest stores of action-potential that mediate dispositions and agencies’ (p. 16). Spinuzzi, Bodrožić, Scaratti, and Ivaldi (2019, p. 119) introduced Adler and Heckscher’s (2007) typology of communities between between Gemeinschaft meaning community and Gesellschaft meaning society: ‘[W]hereas Gemeinschaft relies on personal bonds of loyalty and values of honor and duty, Gesellschaft relies on consistent, rational, individualistic action.’…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent literature on coworking highlighted the role of socially motivated community-building in these novel workspaces. Coworkers generate more than a ‘sense of community’ (Garrett et al, 2017), namely also rituals, routines and mechanisms of co-discipline that produce a degree of organizationality (Blagoev et al, 2019) and an ‘affective commons’ (Waters-Lynch & Duff, 2019) understood as affective atmospheres acting as ‘manifest stores of action-potential that mediate dispositions and agencies’ (p. 16). Spinuzzi, Bodrožić, Scaratti, and Ivaldi (2019, p. 119) introduced Adler and Heckscher’s (2007) typology of communities between between Gemeinschaft meaning community and Gesellschaft meaning society: ‘[W]hereas Gemeinschaft relies on personal bonds of loyalty and values of honor and duty, Gesellschaft relies on consistent, rational, individualistic action.’…”
Section: Discussionmentioning
confidence: 99%
“…This psychological view has informed studies of coworking, which have observed a voluntary ‘contributorship’ to a community among coworkers (Blagoev et al, 2019), next to diminishing work–life boundaries (Spinuzzi, 2012), experiments with sharing practices (Gandini, 2015) and commons-based organizing (Vidaillet & Bousalham, 2020). Furthermore, drawing upon the affective turn (Gregg & Seigworth, 2010), community is understood in terms of atmospheres (Gregg, 2018), affective commons (Waters-Lynch & Duff, 2019) and affective rhythms (Katila, Kuismin, & Valtonen, 2019). In this regard, Waters-Lynch and Duff (2019, p. 5) offer ‘an alternative explanation for the ambivalence documented in so much of the coworking literature, rooted in the shared production of affect and atmospheres, and their management as a common resource vulnerable to depletion, dispersal, commodification and capture’.…”
Section: Control Dynamics In New Collaborative Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, future research in this direction bring in more spatial and regional aspects which are particularly important when the knowledge needed for the venture evolution is sticky or embedded in a local space (Mudambi et al 2018). The consideration of local contexts also ties in with novel developments with respect to the use of makerspaces and coworking-spaces by incumbent firms (Halbinger 2018;Waters-Lynch and Duff 2019). For improving the innovation potential, incumbent firms tend to use makerspaces and coworking-spaces of external providers or to establish internal coworking-spaces in which they allocate entrepreneurial or innovative projects (Spreitzer et al 2015;Bouncken et al 2020).…”
Section: Co-citation Analysismentioning
confidence: 99%
“…In terms of initial engagements, studies have shown, for example, how, under corporate planning, healthcare organizations purposefully attract and retain workers and clients by instilling particular affective atmospheres of competent, timely, energetic and passionate care (Ducey, 2007; Martin et al., 2019; Solomon, 2011). Other studies meanwhile have considered the atmospheres of well‐being, collaboration, community and creativity that emerge in novel working scenarios and spaces, such as with ‘coworking’ (Robelski et al., 2019; Waters‐Lynch & Duff, 2019).…”
Section: Future Inquiries: Health In the New Capitalismmentioning
confidence: 99%